Fatores associados à utilização dos serviços de saúde pela população em situação de rua - Thiago Gomes Gontijo (2022)
Introduction: Growing evidence suggests that the use of health services reveals important inequalities, such as health inequalities, which are a central theme of discussions involving public policies in different nations. The growth in the number of people living on the streets, due to the political, economic and social crisis that affects the country, added to the advent of the COVID 19 pandemic, in 2020, brings with it experiences of violence and marginalization that can increase the difficulties of access and use of basic services, such as health, social assistance, housing, education and leisure. Objective: To analyze the association of sociodemographic, economic and living conditions with the use of health services by the homeless population in Belo Horizonte/Minas Gerais (MG). Methods: This is a cross-sectional, analytical study with a quantitative approach. Data were collected from a sample of 390 homeless people aged 18 years or over who make the Center-South region of Belo Horizonte their living space, through a questionnaire on sociodemographic characteristics, living conditions and use of health services. Data analysis was performed using Pearson's chi-square test, prevalence ratio with a 95% confidence interval. Poisson regression was performed to verify associations with the use of health services. Results: It was found that most people living on the streets are male, aged between 18-84 years, brown, unemployed, among the reasons for being on the street, the main one cited was due to financial conditions and 74.9% self-rated their health status as good. 60% of respondents reported having sought some health service in the last 30 days prior to the interview, of these, 94.3% considered they had been attended. 57.5% said they sought care in Primary Health Care, especially those with some disease/comorbidities (PR = 1.30; 95%CI: 1.07 - 1.56), who use the hostel for overnight stays (PR = 1.62; 95%CI: 1.20 - 2.20) and individuals who reported using medication (PR = 1.22; 95%CI: 1.01 - 1.47). Using Poisson regression, it was possible to identify significant associations between the reason for going to the street, participation in a social movement, self-assessment of health status, use of crak and medication with the use of health services. Conclusions: Such evidence has contributed to improving the understanding of the complex relationship between sociodemographic factors and living conditions with the use of health services by the homeless population, so that the recognition of these factors is essential for expanding access and use of health services. health services and the implementation of emancipatory public policies.